Struggles of Professionalism and Emotional Labour in Standardized Mental Health Care - Kamp, Annette; Dybbroe, Betina (Nordic Journal of Working Life Studies, 2016)
This article points out how recent public sector reforms under headings as New Public Management, Lean and Quality Reforms entail different forms for standardization, and examines how this development instigates a transformation of interdisciplinary and highly skilled emotional labor in mental healthcare. It is based on an ethnographic study of a Danish child psychiatric unit, which ‘produces’ diagnoses and treatment/therapy for children and their families. We illustrate how the enforcement of standardization upsets the balance between the humanistic and medical aspects of psychiatry as a discipline and field of practice, and show how this development challenges professional identities, interdisciplinary collaboration and hierarchical relations. The development is however negotiated, reformulated, and opposed, in teams of mental health professionals. In this context of increasing standardization, highly skilled emotional labor unfolds. We point out how acceleration and leaning of work procedures increases the emotional labor in relation to clients, partners, and colleagues. But paradoxically, at the same time, emotional labor becomes still more invisible as it is excluded from the standardized schemes. The study illustrates the crucial role of emotional labor in mental care work and points out how it is left to the professionals to negotiate paradoxes and make ends meet.